2023
DOI: 10.3390/electronics12112407
|View full text |Cite
|
Sign up to set email alerts
|

Review of Transformer Health Index from the Perspective of Survivability and Condition Assessment

Abstract: As a critical indicator for assessing the survivability and condition of transformers in a fleet, the transformer health index has attracted attention from both asset owners and international organizations like CIGRE and IEEE DEIS/PES. To provide a systematic and comprehensive review for further study or to guide transformer asset management, this paper summarizes the state-of-the-art of the transformer health index, from the early proposed weighted-score-sum approaches to the more recently proposed artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 84 publications
0
1
0
Order By: Relevance
“…The data gathered from the transformer’s historical events, conducted tests, as well as visual inspection is utilized to forecast imminent failures and EOL of each transformer, and according to these factors, a decision is made to prioritize transformers for repair, maintenance, or replacement if a transformer has reached its EOL 69 . Figure 3 demonstrates the primary descriptive framework of the approach utilized, which relies on HI calculations 70 , 71 .
Figure 3 Predicting imminent failures and EOL based on HI and historical data.
…”
Section: Methods Used To Investigate Transformers In-servicementioning
confidence: 99%
“…The data gathered from the transformer’s historical events, conducted tests, as well as visual inspection is utilized to forecast imminent failures and EOL of each transformer, and according to these factors, a decision is made to prioritize transformers for repair, maintenance, or replacement if a transformer has reached its EOL 69 . Figure 3 demonstrates the primary descriptive framework of the approach utilized, which relies on HI calculations 70 , 71 .
Figure 3 Predicting imminent failures and EOL based on HI and historical data.
…”
Section: Methods Used To Investigate Transformers In-servicementioning
confidence: 99%
“…The relationships used to determine the total transformer health index HI T and RFL are as follows [3,20,25]:…”
Section: Determination Of the Health Index And Service Life Of The Tr...mentioning
confidence: 99%
“…Several studies have shown that the transformer HI is a factor that uses information from operational studies, field inspections and laboratory tests to provide a reliable decision for the user [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Indeks kesehatan trafo yang diusulkan akan memberikan penilaian kondisi kesehatan trafo yang akan berguna untuk pemeliharaan, memastikan kinerja trafo yang optimal, peningkatan efisiensi dan juga peningkatan waktu hidup yang diharapkan. Berikutnya [4] menyatakan indeks kesehatan transformator dinyatakan dalam bentuk probabilitas, yang dapat dengan mudah memberikan pemahaman kepada staf tentang keadaan transformator dalam penggunaan praktis. Sebelum menghitung indeks kesehatan, perlu untuk mendapatkan statistik untuk lokasi kesalahan transformator dan faktor-faktor yang mempengaruhi lokasi ini sesuai dengan faktor-faktor seperti penggunaan transformator dan penyebab kesalahan dan untuk membuat diagram asiklik terarah.…”
Section: Pendahuluanunclassified